3D printed near-infrared high-numerical aperture achromatic metalens - Heming Wei; Wenchen Hu; Jingtian Hu; Guoqiang He; Fufei Pang; Sridhar Krishnaswamy; Jan Nedoma; Carlos Marques (iScience)
Summary: Traditional optical Fresnel microlenses have limitations such as large size, limited optical quality for imaging, and low focusing efficiency in achromatic lenses with high NA. In contrast, metalenses rely on their subwavelength structure to modulate the phase distribution, resulting in smaller volumes and superior focusing performance. In this work, we inverse designed and fabricated an achromatic metalens with high-NA and broad wavelength range through direct laser writing using the two-photon polymerization technique. With a focal length of 19 μm, a thickness of 3.6 μm, and a numerical aperture of 0.8, the metalens exhibits an average focusing efficiency of 53.6% and an average half maximum width of 1.27 μm at the working wavelength. The measured average focusing efficiency is 50.4% within the bandwidth range of 1510 nm–1610 nm. The presented work demonstrates the great potential of 3D printing and inverse design for realizing functional meta-devices for aerospace sector.